2015
DOI: 10.1186/s12884-015-0779-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a scale to evaluate midwives’ beliefs about assessing alcohol use during pregnancy

Abstract: BackgroundPrenatal alcohol exposure is an important modifiable cause of adverse fetal outcomes during and following pregnancy. Midwives are key providers of antenatal care, and it is important to understand the factors which influence their ability to provide appropriate advice and support to women about alcohol use in pregnancy. The main aim of this study was to develop a psychometrically valid scale to evaluate midwives’ beliefs about assessing alcohol use during pregnancy.MethodA self-administered questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
2
15
0
1
Order By: Relevance
“…Despite this, previous studies assessing barriers to the adherence of maternal alcohol guideline recommendations have not utilised comprehensive implementation frameworks, and subsequently have focussed on a narrow range of potential barriers that are clinician focused . Nonetheless, the following barriers to the provision of clinical guideline recommendations for maternal alcohol consumption have been reported in the literature: a lack of knowledge or confidence in assessing and advising pregnant women about alcohol consumption; a belief that addressing alcohol will cause discomfort or impact on the client‐clinician relationship; and a lack of training, time or resources . Other factors suggested by implementation frameworks to potentially impede the implementation of clinical guidelines in general, such as a lack of planning in how to deliver the guidelines in consults and a lack of feedback to help improve care provision, have not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, previous studies assessing barriers to the adherence of maternal alcohol guideline recommendations have not utilised comprehensive implementation frameworks, and subsequently have focussed on a narrow range of potential barriers that are clinician focused . Nonetheless, the following barriers to the provision of clinical guideline recommendations for maternal alcohol consumption have been reported in the literature: a lack of knowledge or confidence in assessing and advising pregnant women about alcohol consumption; a belief that addressing alcohol will cause discomfort or impact on the client‐clinician relationship; and a lack of training, time or resources . Other factors suggested by implementation frameworks to potentially impede the implementation of clinical guidelines in general, such as a lack of planning in how to deliver the guidelines in consults and a lack of feedback to help improve care provision, have not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…There have been few studies of what providers know about the effects of prenatal alcohol. Watkins and colleagues () surveyed midwives in Western Australia about assessing alcohol use during pregnancy, including positive and negative consequences of asking and their capacity to assess drinking (Watkins et al., ). They reported that midwives were most positive about their capacity to ask and the effectiveness of asking, and least positive about patients’ knowledge about the effects of alcohol use and their own comfort in asking.…”
mentioning
confidence: 99%
“…They reported that midwives were most positive about their capacity to ask and the effectiveness of asking, and least positive about patients’ knowledge about the effects of alcohol use and their own comfort in asking. Watkins and colleagues () did not assess screening practices, but a prerequisite for screening is an awareness of the potentially damaging effects of alcohol during pregnancy (Floyd et al., ; Goodman and Wolff, ) and belief that screening is effective and acceptable to patients. Yet providers often reported feeling unprepared to educate their pregnant patients about the risks of prenatal alcohol because they themselves do not fully understand the effects.…”
mentioning
confidence: 99%
“…Fears may include potential charges of child abuse, as is the case under civil child welfare statutes in 18 states, or civil commitment in 3 states . Clinicians may struggle to balance the need to address alcohol use in pregnancy with their fear that this discussion could create distrust among the women in their care …”
Section: Screening For At‐risk Alcohol Usementioning
confidence: 99%
“…24 Clinicians may struggle to balance the need to address alcohol use in pregnancy with their fear that this discussion could create distrust among the women in their care. 25 Four tools clinicians should consider for use in prenatal care settings include the 1) AUDIT-C; 2) Tolerance, Annoyed, Cut-Down, Eye-Opener (T-ACE) test; 3) Tolerance, Worried, Eye-opener, Amnesia, and Cut-Down (TWEAK) test; and 4) One-Question Prenatal Alcohol Use Assessment ( Table 1).…”
Section: Part Amentioning
confidence: 99%